The Relationship of Body Composition and Sleep Quality with VO2max in Adolescent Athletes at Sidoarjo Sports High School and Sewon 1 High School - Fathirani Mutiara; Rahadyana Muslichah; Mirza Hapsari Sakti Titis Penggalih (Amerta Nutrition)
Background: Body composition and sleep quality are body components that need to be considered in adolescent athletes. Both components can affect the level of maximum oxygen volume (VO2max) and become factors in increasing physical performance in adolescent athletes.